166k views
5 votes
Enter the value for x that makes the quation.

-2(x+3)-1=9

User Rauf
by
4.9k points

2 Answers

3 votes

x= -8

x=-8 because when you distribute -2 with x and 3, you get -2x -6, and that will give you the simplified version: -2x-7=9

You add 7 to both sides so that the 7 cancels out, and you get -2x=16

Then, you divide -2 by both sides to get x by itself, and the result is x= -8


User Abrunet
by
6.1k points
0 votes

Answer: -8


Step-by-step explanation: First add one to both sides. Now you're left with −2(x+3)=10. Then divide both sides by 2 and simplify 10/2 to 5. Next, subtract 3 from both sides (-5-3). Finally, -5-3 is 8 because -5-3 is the same as -5+-3. When you add 5+3, you get 8. However, since your adding two negatives, you end up with -8. I hope this helped you!!!!!!


User Cristallo
by
5.3k points